Adaptive P&O-fuzzy control MPPT for PV boost dc-dc converter - Mohd Zainuri, Muhammad Ammirrul Atiqi; Mohd Radzi, Mohd Amran; Che Soh, Azura; Abd Rahim, Nasrudin (IEEE, 2012)
This paper proposes an adaptive perturb and observe (P&O)-fuzzy control maximum power point tracking (MPPT) for photovoltaic (PV) boost dc-dc converter. The proposed technique combines both advantages of P&O and fuzzy logic technique. P&O is known as very simple and widely used in the market and fuzzy is also simple and provides fast response. Combination of them should improve MPPT’s performance especially with existing of noise. For comparative evaluation, conventional P&O and conventional fuzzy logic have been developed. All the algorithms together with PV module of Kyocera KD210GH-2PU connected to PV boost dc-dc converter were simulated in MATLAB-Simulink respectively. Performance assessment covers overshoot, time response, oscillation and stability as described further in this paper.